Occult Disseminated Metastatic Breast Carcinoma Presenting As Acquired Thrombotic Thrombocytopenic Purpura - Siew Lian Chonga,; Prof. Madya Dr. Asral Wirda Binti Ahmad Asnawi; Roszymah Hamzah; Pek Kuen Liewa; Tee Chuan Ong; Sen Mui Tan; Kian Meng Chang (S. Karger AG, 2024)
Indexed by Scopus